Kedudukan Peradilan Anak Dalam Sistem Hukum Di Indonesia - Wiwin Andini (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2023)
Law No. 4 of 2004, article 10 paragraph (2) has determined that judicial bodies including general courts, religious courts, military courts and state administrative courts are courts under the Supreme Court. The law differentiates between these judicial bodies, each of which has the authority to adjudicate and includes first-level and appellate-level judicial bodies. That in the legal system there are different terms, namely general court and special court. General and special justice is due to the existence of certain cases and groups. General justice is justice for society in general, namely civil cases and criminal cases. Meanwhile, the judiciary is special because it tries certain cases such as religious, military and state administrative courts. Law No. 4 of 2004 articles 10 and 15 explain that children's courts are special courts. This is its specialization and differentiation below the district court. However, in Indonesia there is no place for a juvenile court that stands alone as a special court. so that children's cases are still under the scope of general justice.